EcoGold Monitor: An IoT-Based System for Real-Time Vermicompost Monitoring (Open International Journal of Informatics, 2025)
EcoGold Monitor, an Internet of Things (IoT)-based system designed for real-time compost and soil condition monitoring. The prototype employs an ESP32 microcontroller integrated with a DS18B20 digital temperature sensor and a capacitive soil moisture sensor to collect composting data, environmental data pertinent to plant health and precision agriculture. Sensor data are acquired periodically and transmitted over Wi-Fi to the Blynk IoT platform, which provides cloud-based visualization, logging, and remote access through a web or mobile interface. To enhance user accessibility, the system incorporates WiFiManager, enabling dynamic network configuration without hardcoded credentials. This feature allows non-technical users to connect the device to any available Wi-Fi network through a temporary access point interface. Data are visualized in real-time via graphs and historical logs, allowing users to make informed decisions regarding irrigation scheduling and microclimate management.
Keywords: Internet of Thing (IoT); Microcontroller; Soil moisture sensor; Temperature sensor; Agriculture